LEGAL PROTECTION OF THE PRESIDENT IN A SOVEREIGN STATE FROM THE PERSPECTIVE OF SIYASAH DAULIYAH (A CASE STUDY OF THE ARREST OF THE PRESIDENT OF VENEZUELA): LEGAL PROTECTION OF THE PRESIDENT IN A SOVEREIGN STATE FROM THE PERSPECTIVE OF SIYASAH DAULIYAH (A CASE STUDY OF THE ARREST OF THE PRESIDENT OF VENEZUELA) - Muhammad Rahmat Ridha; Afifa Rangkuti (PENA LAW: International Journal of Law, 2026)
State sovereignty and head of state immunity are fundamental principles of international law, shielding heads of state from foreign court jurisdiction under the doctrine *par in parem non habet imperium*. This study examines the legal protection afforded to a president as head of state and reviews the U.S. arrest of Venezuelan President Nicolás Maduro through the lenses of international law and Siyasah Dauliyah. Using a normative legal method with statutory and conceptual approaches, the research finds that Maduro’s arrest carried out via a unilateral military operation without UN Security Council authorization and without due international legal process violates Article 2(4) of the UN Charter and contravenes customary international law on head of state immunity. From the Siyasah Dauliyah perspective, the head of state embodies political authority and state sovereignty; thus, any action against him constitutes an action against the state itself. The principles of equality, justice, human dignity, and peace, which underpin international relations in *Siyasah Dauliyah*, reject intervention and the use of force against other states. Consequently, legal protection for a president as head of state is inseparable from safeguarding national sovereignty and upholding the non‑intervention principle in international affairs. Any breach of this protection not only undermines the rule of law but also threatens global stability and the mutual respect that sovereign states owe one another.